Carbonic maceration as a value creation strategy for geographical indication coffee in Indonesia - HALIL HALIL; KURNIAWAN M. NUR; DRIYANTO WAHYU WICAKSONO (Asian Journal of Agriculture, 2026)
Abstract. Halil, Nur KM, Wicaksono DW. 2026. Carbonic maceration as a value creation strategy for geographical indication coffee in Indonesi. Asian J Agric 10 (1): g100117. https://doi.org/10.13057/asianjagric/g100117. Carbonic Maceration (CM) has emerged as a promising post-harvest innovation for speciality coffee, yet evidence on its economic contribution at the farm level remains limited. This study analyses the economic impact of applying Carbonic Maceration (CM) post-harvest technique to Ijen-Raung Arabica coffee, a Geographical Indication (GI) protected commodity from Bondowoso, Indonesia. Using a quantitative approach, data were collected from 15 farmers within the Bondowoso GI Protection Association (PMPIG) during June-August 2025. The analysis integrated Economic Value Added (EVA) and Hayami Method frameworks to assess financial performance, value creation, and income distribution. Results demonstrate that CM generates substantial economic value, with an EVA of IDR 5,946,424.74 per hectare annually, confirming genuine value creation beyond cost of capital. Hayami's analysis revealed the added value of IDR 36,511.25±4,810.85 per kg (45.13±3.49% ratio), with 70.45±11.36% distributed as labour income, underscoring both profitability and equitable rural development. A critical finding was the 20.63% mass loss before processing, reducing the overall harvest-to-bean conversion to approximately 49.21%, highlighting the need for supply chain optimisation alongside CM adoption. The research novelty lies in its integrative methodology, being the first to combine EVA and Hayami Method to empirically quantify economic returns of post-harvest innovation in a GI coffee system. These findings highlight carbonic maceration as a viable post-harvest strategy for value enhancement and recommend broader adoption supported by capacity building, financial access, and quality-based market linkages.